2009
DOI: 10.3325/cmj.2009.50.583
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perception and Cardiovascular Risk Factors in Patients with Type 2 Diabetes: Cross-sectional Questionnaire Study

Abstract: AIM. To investigate illness perception in patients with type 2 diabetes mellitus and its association with the degree of control over relevant cardiovascular risk factors. METHODS. A cross-sectional questionnaire-based study was performed from June 2007 to March 2008. A stratified random sample of 46 Croatian general practitioners was asked to select, using systematic sampling, the first 6 patients with type 2 diabetes mellitus aged > or =18 years who visited them for consultation during the study period. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 19 publications
6
40
2
Order By: Relevance
“…Kolodinsky and colleagues (2007), who studied knowledge of dietary guidelines and food choice in college students in the USA, reported that increased knowledge of dietary guidelines was positively associated with the consumption of a healthier diet [21]. In addition Petricek and colleagues (2009) who studied illness perception and its effect on the degree of control of cardiovascular risk factors in type 2 diabetics in Croatia, reported that patients who reported deviating from their dietary plan had poorer knowledge about their disease [19]. The results of the present study showed that respondents who reported paying more attention to their diet achieved higher CHD knowledge scores.…”
Section: Factors Associated With Chd Knowledgementioning
confidence: 96%
See 2 more Smart Citations
“…Kolodinsky and colleagues (2007), who studied knowledge of dietary guidelines and food choice in college students in the USA, reported that increased knowledge of dietary guidelines was positively associated with the consumption of a healthier diet [21]. In addition Petricek and colleagues (2009) who studied illness perception and its effect on the degree of control of cardiovascular risk factors in type 2 diabetics in Croatia, reported that patients who reported deviating from their dietary plan had poorer knowledge about their disease [19]. The results of the present study showed that respondents who reported paying more attention to their diet achieved higher CHD knowledge scores.…”
Section: Factors Associated With Chd Knowledgementioning
confidence: 96%
“…[17] have aimed to increase the general public's awareness of CHD in the UK, however, it would appear that more tailored campaigns may be required [9,11,18] since different individuals have marked differences in their baseline knowledge [7]. Although knowledge alone is insufficient, it is a known prerequisite for making decisions about health [19,20], as the majority of the decisions on health behaviours (i.e. exercising more, quitting smoking, eating healthily, etc.)…”
Section: Lack Of Knowledge Of Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…People exhibit a wide variety of ways to cope with their health threats, and personal beliefs seem to be associated with the degree of control they have over their illness [4][5][6]. The degree to which patients follow advice is determined by their health beliefs (Illness Representations or Personal Models), and treatment outcomes depend upon many variables closely related to habits in the case of chronic diseases, where the results depend to a great extent upon human behaviour [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The same result was reported by Broadbent et al (2006) about the BIPQ score. Our results of perception measurements are better results compared with Petriček et al (2009), who showed that the perception measurement obtained worse results in all domain measurements.…”
Section: Discussionmentioning
confidence: 44%